IMPLEMENTATION OF NUTRITION FULFILLMENT TO WOMAN DETAINEES AND PRISONERS AS A FORM OF HEALTH SERVICES IN PURWOREJO CLASS IIB DETENTION CENTER - Kurniawan, Dhoni Tegar; Soge, Markus Marselinus (Journal of Management Small and Medium Enterprises (SMEs), 2025)
The right to obtain proper food in accordance with nutritional standards is one of the fulfillments of human rights by detainees and prisoners in Purworejo Class IIB Detention Center. The fulfillment of food with nutritional standards to women prisoners and inmates should not be equated with male prisoners and detainees. In writing this thesis, it aims to find out how the implementation of nutritional fulfillment for women prisoners and inmates in the Purworejo Class IIB Detention Center is affected by obstacles. This research uses qualitative methods with primary data sources collected by observation, interview, and document study techniques; then the data is analyzed descriptively and qualitatively. In this study, the analysis of health service theory and the concept of balanced nutrition. The first research result shows that the implementation of nutritional fulfillment for women detainees and prisoners in Purworejo Class IIB Detention Center is carried out through hygiene certification from the Purworejo Regency Health Office, selecting kitchen assistants who understand nutritious food, providing tools and supporting facilities that are hygienic in processing food ingredients, processing food ingredients based on SOPs to ensure food quality following standards, and providing a Pratama clinic as a means of supporting the implementation of nutritional fulfillment properly. The results of the second study show that there are still obstacles, namely, the absence of a nutritionist and the small condition of the kitchen of Purworejo Class IIB Detention Center. Keywords: Implementation; Nutrition; Health Services; Woman